Polystyrene resin extruded foam and method for producing the same
Patent Information
- Application Number
- JP2025057578
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明にかかるポリスチレン系樹脂押出発泡体の製造方法によれば、断熱性が高くかつ大きな厚みを有し、美麗な表面を有するポリスチレン系樹脂押出発泡体を提供できる。
Smart Images

Figure 2026165276000001 
Figure 2026165276000002 
Figure 2026165276000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a polystyrene resin extruded foam and a method for producing the same. [Background technology]
[0002] Polystyrene resin extruded foam is used as insulation material in houses, buildings, and cold storage facilities due to its high thermal insulation properties. Styrene resin extruded foam is manufactured by melting and kneading a composition containing polystyrene resin and a blowing agent in an extruder, and then extruding it into a low-pressure range through slits in a die or the like.
[0003] As a method to improve the thermal insulation properties of polystyrene resin extruded foams, the use of alkyl chlorides such as methyl chloride and ethyl chloride as blowing agents has been proposed (for example, Patent Documents 1-3). By using a gas with low thermal conductivity (high thermal insulation properties) such as alkyl chloride as a blowing agent, the gas with low thermal conductivity is sealed within the foam's bubbles, thereby improving the foam's thermal insulation properties. Furthermore, a technique has been proposed to increase the thickness of the foam by using alkyl chloride and water in combination as blowing agents (for example, Patent Document 4). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2005-330351 [Patent Document 2] Japanese Patent Publication No. 2019-108416 [Patent Document 3] Japanese Patent Publication No. 2019-189811 [Patent Document 4] Japanese Patent Publication No. 2024-141462 [Overview of the project] [Problems that the invention aims to solve]
[0005] When alkyl chloride and water are used together as foaming agents, there is a problem that equipment corrosion is likely to progress, and an acid neutralizing agent is added to solve this problem. However, when an acid neutralizing agent is used, there is a problem that pores tend to form on the surface of the foam.
[0006] Therefore, the present invention aims to provide a styrene-based resin extruded foam that has high thermal insulation properties and does not have pores on its surface. [Means for solving the problem]
[0007] To solve the above problems, the inventors conducted diligent research and discovered that, in a form using alkyl chloride and water as foaming agents, the generation of pores (voids) caused by acid neutralizers can be suppressed by adding a specific nitrogen-containing compound, thus completing the present invention. The present invention includes the following embodiments.
[0008] The present invention (1) A method for producing a styrene resin extruded foam, comprising melt-kneading a composition containing a styrene resin and a foaming agent, and extruding it to a low-pressure range to form a foam, The foaming agent comprises at least alkyl chloride and water. The aforementioned composition further comprises an acid neutralizing agent. The composition further comprises a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives. Method for producing polystyrene resin extruded foam, (2) The method for producing a polystyrene resin extruded foam according to (1), wherein the amount of a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and derivatives thereof in the composition is 0.1 parts by weight or more per 100 parts by weight of the styrene resin, (3) A method for producing a polystyrene resin extruded foam according to any one of (1) to (2), wherein the amount of alkyl chloride in the composition is 1 to 8 parts by weight per 100 parts by weight of the styrene resin. (4). The blowing agent further contains a hydrofluoroolefin and / or a hydrochlorofluoroolefin, and the total added amount of the hydrofluoroolefin and / or the hydrochlorofluoroolefin is 0.5 parts by weight or more and 10.0 parts by weight or less relative to 100 parts by weight of the styrenic resin, the method for producing the styrenic resin extruded foam according to any one of (1) to (3), (5). The composition contains graphite, The graphite is contained in an amount of 1.0 parts by weight or more and 5.0 parts by weight or less relative to 100 parts by weight of the styrenic resin, the method for producing the styrenic resin extruded foam according to any one of (1) to (4), (6). The thermal conductivity of the foam is 0.0284 W / mK or less, the method for producing the polystyrene-based resin extruded foam according to any one of (1) to (5), (7). The thickness of the foam is 10 mm or more, the method for producing the polystyrene-based resin extruded foam according to any one of (1) to (6), . [Effects of the Invention]
[0009] According to the method for producing a polystyrene-based resin extruded foam of the present invention, a polystyrene-based resin extruded foam having high heat insulating properties, a large thickness, and a favorable surface can be provided. [Modes for Carrying Out the Invention]
[0010] The polystyrene-based resin extruded foam of the present invention (hereinafter sometimes referred to as "the foam of the present invention") is produced by melt-kneading a composition containing a polystyrene-based resin and a blowing agent to obtain a foamable molten composition, and extruding the foamable molten composition into a low-pressure region for foam molding.
[0011] [Composition] The foaming molten composition contains a polystyrene resin and a blowing agent, as well as a flame retardant and a stabilizer, and optionally includes additives such as flame retardant enhancers, radiation suppressants, lubricants, water absorbers, and moldability improvers. The following describes in detail each component of the foaming molten composition (sometimes simply referred to as "the composition"). Unless otherwise specified, each component described below may be used individually or in combination of two or more.
[0012] <Polystyrene resin> Polystyrene resins contain styrene polymers. Examples of styrene polymers include homopolymers of styrene monomers (polystyrene); copolymers of two or more styrene monomers; and copolymers of styrene monomers with other monomers. When the styrene polymer is a copolymer, the amount of styrene monomer in the total monomer is preferably 60% by weight or more, and more preferably 70% by weight or more. The polymer sequence of the copolymer is not particularly limited and may be either a random copolymer or a block copolymer. The copolymer may also be a graft copolymer. The styrene polymer may also be a polymer having a branched structure.
[0013] Examples of styrene monomers include styrene, methylstyrene, dimethylstyrene, ethylstyrene, diethylstyrene, isopropylstyrene, bromostyrene, dibromostyrene, tribromostyrene, chlorostyrene, dichlorostyrene, trichlorostyrene, vinyltoluene, and vinylxylene. Other monomers include polyfunctional vinyl compounds such as divinylbenzene; acrylic acid and methacrylic acid; (meth)acrylic acid ester compounds such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, and butyl methacrylate; vinyl cyanide compounds such as (meth)acrylonitrile; diene compounds such as butadiene; unsaturated carboxylic acid anhydrides such as maleic anhydride and itaconic anhydride; and N-alkyl-substituted maleimide compounds such as N-methylmaleimide, N-butylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, N-(2)-chlorophenylmaleimide, N-(4)-bromophenylmaleimide, and N-(1)-naphthylmaleimide.
[0014] As for polystyrene-based resins, polystyrene, styrene-acrylonitrile copolymer, styrene-(meth)acrylic acid copolymer, styrene-maleic anhydride copolymer, and styrene-diene compound copolymer (impact-resistant polystyrene, for example, styrene-butadiene copolymer) are preferred from the viewpoint of being relatively inexpensive and suitable for extrusion foam molding.
[0015] The polystyrene resin may contain polymers other than styrene polymers, such as polyolefins, acrylic polymers, polyesters, and polyphenylene ethers, to the extent that they do not adversely affect the effects of the present invention. When the polystyrene resin contains polymers other than styrene polymers, the content is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, even more preferably 5 parts by weight or less, and may be 3 parts by weight or less or 1 part by weight or less, per 100 parts by weight of the styrene polymer.
[0016] Polystyrene resins may be mixtures of two or more polymers with different copolymer components, molecular weights, molecular weight distributions, branched structures, melt flow rates, etc., for the purpose of adjusting the melt viscosity, melt flow rate, melt tension, etc., during molding.
[0017] The polystyrene resin may be commercially available polystyrene resin (so-called virgin resin), or recycled polystyrene resin (for example, recycled polystyrene resin that has been recycled using a recycled extruder after being used in the manufacture of foams, etc., and recycled polystyrene resin recycled from food trays and fish boxes collected from the market, etc.). Virgin resin and recycled polystyrene resin may be mixed.
[0018] The melt flow rate (MFR) of polystyrene resins, as measured according to JIS K7210, is preferably 50 g / 10 min or less. An MFR of 50 g / 10 min or less allows for uniform dispersion of the foaming agent within the polystyrene resin during melt-mixing, enabling stable extrusion and foam molding, thus improving production stability. The MFR of polystyrene resins may also be 0.5 to 40 g / 10 min, or 1 to 30 g / 10 min.
[0019] <Foaming agent> The foam of the present invention uses alkyl chloride and water as blowing agents. By using alkyl chloride and water as blowing agents, it is possible to provide a polystyrene resin extruded foam that has high thermal insulation properties, a large thickness, and a beautiful surface.
[0020] As alkyl chlorides, methyl chloride or ethyl chloride are preferred because they have low thermal conductivity in the gaseous state and contribute significantly to improving heat insulation.
[0021] The amount of alkyl chloride used is preferably 1 to 8 parts by weight, more preferably 2 to 7 parts by weight, and even more preferably 2.5 to 5 parts by weight, per 100 parts by weight of polystyrene resin. If the amount of alkyl chloride is too small, the effect of improving the heat insulation properties due to alkyl chloride may not be fully realized. On the other hand, if the amount of alkyl chloride is excessively large, the plasticizing effect on the styrene resin may be large, which may cause a decrease in the heat resistance and strength of the foam.
[0022] By using water as a blowing agent, bubbles with relatively large diameters are more easily formed, thus enabling the creation of thicker foams. The amount of water used is preferably 0.1 to 3 parts by weight, more preferably 0.3 to 2 parts by weight, and even more preferably 0.4 to 1.5 parts by weight, per 100 parts by weight of polystyrene resin. If the amount of water is too small, it may be difficult to obtain a thicker foam. On the other hand, if the amount of water is excessively large, coarse bubbles are more likely to form, and pores may be generated, which may result in poor appearance of the foam and a decrease in its thermal insulation properties.
[0023] In addition to alkyl chloride and water, other blowing agents capable of functioning as blowing agents may be used. For example, the use of hydrofluoroolefins and / or hydrochlorofluoroolefins as blowing agents tends to further improve the thermal insulation properties of extruded foams.
[0024] As a hydrofluoroolefin, tetrafluoropropene is preferred due to its low thermal conductivity as a gas and high safety. Specific examples of tetrafluoropropene include 1,3,3,3-tetrafluoropropene (HFO-1234ze) and 2,3,3,3-tetrafluoropropene (HFO-1234yf). As a hydrochlorofluoroolefin, hydrochlorotrifluoropropene is preferred due to its low thermal conductivity as a gas and high safety. Specific examples of hydrochlorotrifluoropropene include 1-chloro-3,3,3-trifluoropropene (HCFO-1233zd).
[0025] When using hydrofluoroolefins and / or hydrochlorofluoroolefins as blowing agents, from the viewpoint of improving the thermal insulation properties of the foam, the amount used (total of hydrofluoroolefins and hydrochlorofluoroolefins) is preferably 0.5 to 10 parts by weight, but may also be 0.5 to 9 parts by weight or 1.0 to 8.0 parts by weight, per 100 parts by weight of polystyrene resin. The more hydrofluoroolefins and hydrochlorofluoroolefins used, the better the thermal insulation properties of the foam tend to be. On the other hand, even if the amount of hydrofluoroolefins and hydrochlorofluoroolefins used is excessively large, a significant improvement in thermal insulation properties cannot be expected. Furthermore, if the amount of hydrofluoroolefins and hydrochlorofluoroolefins used is excessively large, the blowing agent may separate from the resin molten material, causing spot holes to form on the surface of the foam or reducing the closed-cell ratio, which can impair thermal insulation properties.
[0026] Examples of foaming agents other than those listed above include: saturated hydrocarbons with 3 to 5 carbon atoms such as propane, n-butane, isobutane, n-pentane, isopentane, and opentane; alcohols with 1 to 4 carbon atoms such as ethanol, methanol, propyl alcohol, isopropyl alcohol, butyl alcohol, isobutyl alcohol, and t-butyl alcohol; dimethyl ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, furfural, 2-methylfuran, tetrahydrofuran, and tetrahydropyl ether. Examples include ethers such as or; ketones such as dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, methyl-i-butyl ketone, methyl-n-amyl ketone, methyl-n-hexyl ketone, ethyl-n-propyl ketone, and ethyl-n-butyl ketone; organic blowing agents represented by carboxylic acid esters such as methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, methyl propionate, and ethyl propionate; inorganic blowing agents such as carbon dioxide; azo compounds; and chemical blowing agents such as tetrazoles.
[0027] Among these exemplary blowing agents, saturated hydrocarbons having 3 to 5 carbon atoms have a plasticizing effect on polystyrene resins and enhance the fluidity of the molten composition, thus contributing to a reduction in the load on the extruder. From the viewpoint of foaming properties, propane, n-butane, and isobutane are preferred among saturated hydrocarbons having 3 to 5 carbon atoms, and from the viewpoint of the thermal insulation properties of the foam, n-butane and isobutane are particularly preferred.
[0028] When using saturated hydrocarbons having 3 to 5 carbon atoms as a blowing agent, from the viewpoint of improving the heat insulation properties of the foam, the amount of saturated hydrocarbons having 3 to 5 carbon atoms used is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, even more preferably 0.7 parts by weight or more, and may be 0.9 parts by weight or more or 1 part by weight or more, per 100 parts by weight of polystyrene resin. On the other hand, from the viewpoint of suppressing molding defects such as bubble bursting, the amount of saturated hydrocarbons having 3 to 5 carbon atoms used is preferably 5 parts by weight or less, more preferably 4.5 parts by weight or less, and may be 4 parts by weight or less or 3.5 parts by weight or less, per 100 parts by weight of polystyrene resin.
[0029] The amount of blowing agent used (total amount of all blowing agents) is preferably 2 to 20 parts by weight, more preferably 3 to 15 parts by weight, even more preferably 4 to 12 parts by weight, and may also be 5 to 10 parts by weight, per 100 parts by weight of polystyrene resin. If the amount of blowing agent used is within the above range, the foaming power of the composition is ensured, and a polystyrene resin foam with the desired thickness can be stably obtained.
[0030] <Acid neutralizer> In the present invention, the composition includes a polystyrene resin, alkyl chloride as a foaming agent, and water, in addition to an acid neutralizing agent. By including an acid neutralizing agent in the composition used to produce the foam, the generation and diffusion of corrosive gases due to the reaction between alkyl chloride and water can be suppressed, thereby preventing equipment deterioration.
[0031] As an acid neutralizing agent, any compound capable of neutralizing acid can be organic or inorganic. Examples of organic compounds include amines. Examples of inorganic compounds include oxides, hydroxides, carbonates, bicarbonates, and silicates of alkali metals or alkaline earth metals. Among these, inorganic compounds are preferred because they have little effect on foaming properties and the physical properties of the foam.
[0032] As described later, it is preferable to dissolve the acid neutralizer in water as a foaming agent and add it to the composition. For this reason, it is preferable that the acid neutralizer is water-soluble, and preferably dissolves in water at room temperature in an amount of 1% by weight or more. Alkali metal salts are preferred as acid neutralizers because they have high water solubility and excellent acid neutralizing properties. Among these, carbonates and bicarbonates are preferred because they do not leave salt residue and have little effect on foaming properties and the physical properties of the foam. Examples of alkali metal carbonates and bicarbonates include lithium carbonate, lithium bicarbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate. Among these, alkali metal carbonates are preferred because they are easy to handle, and sodium carbonate and potassium carbonate are particularly preferred.
[0033] When alkyl chloride and water are used together as a blowing agent, if the alkyl chloride and water come into contact and mix during the injection of the blowing agent or inside the extruder after injection, acidic gases such as hydrogen chloride are generated. These acidic gases can cause corrosion of metals such as extruders and piping. By adding an acid neutralizing agent to the composition, the acidic gases are neutralized, thereby suppressing corrosion of the equipment.
[0034] The amount of acid neutralizer is preferably 0.003 times or more in molar ratio to the alkyl chloride used as a foaming agent, more preferably 0.005 times or more, even more preferably 0.008 times or more, and particularly preferably 0.01 times or more. A higher amount of acid neutralizer tends to suppress the generation of corrosive gases, thereby enhancing the corrosion prevention effect on the equipment.
[0035] On the other hand, if the amount of acid neutralizer is excessively large, residue of the acid neutralizer may affect the foaming properties and the physical properties of the foam. Therefore, the amount of acid neutralizer is preferably 1 or less in molar ratio to alkyl chloride, more preferably 0.5 or less, even more preferably 0.1 or less, and may be 0.07 or less, 0.05 or less, or 0.03 or less. The amount of acid neutralizer is preferably 2 parts by weight or less, more preferably 1 part by weight or less, even more preferably 0.5 parts by weight or less, and may be 0.3 parts by weight or less, 0.2 parts by weight or less, or 0.15 parts by weight or less per 100 parts by weight of polystyrene resin.
[0036] <Nitrogen-containing compounds> In the present invention, the composition includes a polystyrene resin, a foaming agent, and an acid neutralizing agent, in addition to a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives. By including a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives in the composition used to produce the foam, the generation of pores (voids) in the foam can be suppressed. Note that the nitrogen-containing compound in the present invention is a separate component from tris(2,3-dibromopropyl) isocyanurate, a brominated flame retardant described later.
[0037] Examples of nitrogen-containing compounds include compounds selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives, represented by the following general formulas 1 and 2.
[0038] [ka] [In the formula, R 1 , R 2 , R 3 [These are selected from a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, an organic group represented by -YX (wherein Y is an alkylene group, phenylene group, or cycloalkylene group having 1 to 6 carbon atoms, and X is a monovalent organic group containing an epoxy group, carboxyl group, hydroxyl group, amino group, phenyl group, or phosphorus atom), and a phenyl group, and may be different from each other.]
[0039]
Chemical Formula
[0040] Specific examples of nitrogen-containing compounds include cyanuric acid; monoalkyl cyanurates such as ethyl cyanurate; dialkyl cyanurates such as diethyl cyanurate; trialkyl cyanurates such as trimethyl cyanurate and triethyl cyanurate; phenyl cyanurate; diphenyl cyanurate; triphenyl cyanurate; dialkylphenyl cyanurate such as dimethylphenyl cyanurate; isocyanuric acid; monoalkyl isocyanurate such as methyl isocyanurate; dialkyl isocyanurate such as diethyl isocyanurate; trialkyl isocyanurate such as trimethyl isocyanurate and triethyl isocyanurate; phenyl isocyanurate; diphenyl isocyanurate; triphenyl isocyanurate; dialkylphenyl isocyanurate such as dimethylphenyl isocyanurate; mono(2-aminoethyl) isocyanurate Examples include mono(aminoalkyl) isocyanurates such as rate; di(aminoalkyl) isocyanurates such as di(2-aminoethyl) isocyanurate; tri(aminoalkyl) isocyanurates such as tri(2-aminoethyl) isocyanurate; tri(hydroxyalkyl) isocyanurates such as tri(hydroxymethyl) isocyanurate, tri(2-hydroxyethyl) isocyanurate, tri(2-hydroxypropyl) isocyanurate; di(hydroxyalkyl) isocyanurates such as di(hydroxymethyl) isocyanurate; bis(carboxyalkyl) isocyanurates such as bis(2-carboxyethyl) isocyanurate; 1,3,5-tris(carboxyalkyl) isocyanurate such as 1,3,5-tris(2-carboxyethyl) isocyanurate; and tris(2,3-epoxypropyl) isocyanurate.
[0041] In the present invention, these compounds can be used individually or as a mixture of two or more. Among the nitrogen-containing compounds, cyanuric acid (R in general formula 1) is particularly preferred. 1 , R 2 , R 3 (where R is a hydrogen atom), isocyanuric acid (R in general formula 2) 4 , R 5 , R 6(where R is a hydrogen atom), bis(2-carboxyethyl) isocyanurate (R in general formula 2) 4 is a hydrogen atom, and R 5 , R 6 In this case, Y is an ethylene group and X is a carboxyl group.
[0042] The amount of nitrogen-containing compound used is adjusted as appropriate to achieve a void formation suppression effect, but preferably 0.01 parts by weight or more, more preferably 0.03 parts by weight or more, even more preferably 0.05 parts by weight or more, and particularly preferably 0.1 parts by weight or more, per 100 parts by weight of polystyrene resin. On the other hand, 10 parts by weight or less is preferred, more preferably 5 parts by weight or less, even more preferably 3 parts by weight or less, and particularly preferably 1 part by weight or less. If the nitrogen-containing compound content is below the above range, it tends to be difficult to obtain the void formation suppression effect that is the objective of the present invention, while if it exceeds the above range, it may impair moldability during foam production.
[0043] <Additives> As described above, the composition contains a polystyrene resin, a foaming agent, and an acid neutralizing agent, in addition to a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives. The composition may further contain other additives.
[0044] Examples of additives include water absorbents, heat radiation inhibitors, flame retardants, flame retardant enhancers, flame retardant modifiers (iron oxides, iron complexes, diphenylalkanes, diketones, etc.), lubricants (sodium stearate, calcium stearate, etc.), bubble size modifiers (talc, etc.), stabilizers (epoxy compounds, polyhydric alcohol ester compounds, phenolic antioxidants, phosphite antioxidants, etc.), processing aids (fatty acid metal salts, fatty acid amides, fatty acid esters, liquid paraffin, olefin waxes, etc.), antistatic agents, surfactants, colorants (pigments, dyes, etc.), UV absorbers, fluorescent whitening agents, plasticizers, fillers, and radical generators.
[0045] (Water absorbent) When water is used as a foaming agent, it is preferable that the composition contains a water-absorbing agent. Water has low solubility in polystyrene resins, and if undissolved water is present in the composition, large bubbles are likely to form, which can cause the bubbles to burst. By including a water-absorbing agent in the composition, the solubility of water in the composition is increased, and the water is dispersed uniformly, thereby suppressing molding defects such as the generation and bursting of large bubbles, and enabling stable extrusion foam molding.
[0046] Examples of water-absorbing agents include water-absorbing minerals (smectite, zeolite, etc.), silica, and hydrophilic organic substances. Examples of smectite include natural bentonite, purified bentonite, organically modified bentonite, and hectorite. Examples of zeolite include natural zeolite, artificial zeolite, and synthetic zeolite. Examples of silica include anhydrous silica, modified silica with hydroxyl groups on its surface, and porous silica. Examples of hydrophilic organic substances include polyacrylate polymers, starch-acrylic acid graft copolymers, polyvinyl alcohol polymers, vinyl alcohol-acrylate copolymers, ethylene-vinyl alcohol copolymers, polyacrylonitrile-methyl methacrylate-butadiene copolymers, polyethylene oxide copolymers and their derivatives, polyvinylpyrrolidone, sodium carboxymethylcellulose, hydroxyethylcellulose, polyhydric alcohols, and melamine.
[0047] The amount of water absorbent used can be adjusted as appropriate depending on the amount of water used, etc. The amount of water absorbent in the composition is about 0.01 to 5 parts by weight per 100 parts by weight of polystyrene resin, preferably 0.1 to 3 parts by weight, more preferably 0.2 to 2.5 parts by weight, and may also be 0.3 to 2 parts by weight, or 0.5 to 1.5 parts by weight. The ratio (by weight) of water absorbent in the composition is about 0.05 to 5, preferably 0.1 to 4.5, and may also be 0.2 to 4 or 0.3 to 3.
[0048] (Heat radiation suppressant) To improve the thermal insulation properties of the foam, a heat radiation suppressant may be added to the composition. A heat radiation suppressant is a substance that has the properties of reflecting, scattering, and absorbing electromagnetic waves in the near-infrared or infrared region. The inclusion of a heat radiation suppressant tends to further improve the thermal insulation properties of the foam.
[0049] Examples of heat radiation suppressants include graphite, titanium dioxide, barium sulfate, zinc oxide, aluminum oxide, and antimony oxide, which are white particles. Among these, graphite is particularly preferred due to its high heat radiation suppression effect. Among the white particles, titanium dioxide is particularly preferred.
[0050] Specific examples of graphite include flaky graphite, granular graphite, spheroidal graphite, and artificial graphite. Among these, flaky graphite is preferred because it has a high heat radiation suppression effect. The fixed carbon content of the graphite is preferably 80% or more, and more preferably 85% or more.
[0051] The average particle size of the graphite is preferably 15 μm or less, and more preferably 10 μm or less. A smaller average particle size results in a larger specific surface area and a higher probability of collision with thermal radiation, thus improving the thermal radiation suppression effect. The average particle size of the graphite is determined by measuring and analyzing the particle size distribution using a laser diffraction scattering method based on Mie theory in accordance with ISO 13320:2009 and JIS Z8825:2013, and is the particle diameter (volume-average particle size) at which the cumulative volume relative to the total volume of all particles becomes 50%.
[0052] When using a heat radiation suppressant such as graphite, the amount of heat radiation suppressant in the composition is preferably 0.1 to 6.0 parts by weight, more preferably 0.1 to 5.0 parts by weight, even more preferably 0.5 to 5.0 parts by weight, and 0.8 to 4.0 parts by weight per 100 parts by weight of polystyrene resin. The amount may be 0 parts by weight or 1.0 to 3.5 parts by weight. If the amount of heat radiation inhibitor is too small, a sufficient heat radiation suppression effect cannot be obtained. On the other hand, if the amount of heat radiation inhibitor is too large, the dispersibility in the composition will be poor, and it will be difficult to obtain a heat radiation suppression effect commensurate with the amount. Furthermore, as the content of solid additives such as heat radiation inhibitors increases, the number of nucleation points increases, which tends to make it difficult to give the foam a beautiful surface or obtain a foam with a large thickness, as it reduces the fineness of the bubbles in the foam. Note that solid additives such as heat radiation inhibitors may also be added to the composition as a masterbatch that has been dispersed in a polystyrene resin beforehand.
[0053] (Flame retardants and flame retardant enhancers) As a flame retardant, brominated flame retardants are preferably used. Specific examples of brominated flame retardants include brominated bisphenol compounds such as tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl) ether and tetrabromobisphenol A-bis(2,3-dibromopropyl) ether; aliphatic bromine-containing polymers such as brominated styrene-butadiene block copolymer, brominated styrene-butadiene random copolymer, and brominated styrene-butadiene graft copolymer; tetrabromocyclooctane; hexabromocyclododecane; tris(2,3-dibromopropyl) isocyanurate, etc. The amount of flame retardant used is approximately 0.1 to 10 parts by weight per 100 parts by weight of polystyrene resin, but may also be 0.5 to 8 parts by weight or 1 to 5 parts by weight.
[0054] Examples of flame retardant additives include radical generators such as 2,3-dimethyl-2,3-diphenylbutane and poly-1,4-diisopropylbenzene; phosphate esters; and phosphine oxides.
[0055] [Method for manufacturing foam] For the production of styrene resin extruded foam, an extrusion foaming apparatus is used in which a melt-kneading section and a foam molding section having a die are arranged sequentially from the upstream side to the downstream side in the extrusion direction of the composition. The melt-kneading section and the foam molding section are connected. A cooling section to lower the temperature of the composition may be provided between the melt-kneading section and the foam molding section. Styrene resin extruded foam is produced by melt-kneading a resin composition containing polystyrene resin and a foaming agent (melt-kneading step), and then extruding the foamable molten composition into a low-pressure region for foam molding (foaming step).
[0056] In the melt-mixing process, a resin composition containing polystyrene resin and additives is supplied to the melt-mixing section and mixed. Methods for incorporating various additives into polystyrene resin include, for example, adding various additives to the polystyrene resin and mixing by dry blending; adding various additives to the molten polystyrene resin from a supply section provided in the melt-mixing section; and preparing a masterbatch containing high concentrations of various additives in the polystyrene resin using an extruder, kneader, Banbury mixer, rolls, etc., and then mixing the masterbatch with the polystyrene resin by dry blending.
[0057] Examples of the melt-mixing section include an extruder using a screw. Both single-screw and twin-screw extruders can be used. The screw rotation direction of a twin-screw extruder may be the same or different directions. The heating temperature in the melt-mixing section should be above the melting temperature of the polystyrene resin, and from the viewpoint of suppressing resin degradation, a temperature of approximately 150°C to 260°C is preferred. The melt-mixing time should be appropriately set according to the type of polystyrene resin and the extrusion rate per unit time.
[0058] In the melt-mixing process, a foaming agent is added to the resin composition under high pressure (injected) to prepare a foaming molten composition. The timing of adding the foaming agent is not particularly limited; it can be added at any stage of the melt-mixing process, such as before heating and melting the resin composition, during heating and melting, or after heating and melting the resin composition. The pressure used when injecting the foaming agent should be higher than the internal pressure of the melt-mixing section.
[0059] In the melt-mixing process, after melt-mixing the resin composition and the foaming agent, the foamable molten composition supplied to the foaming process may be cooled within a temperature range in which the composition does not solidify. For example, the composition may be cooled in a cooling section disposed between the melt-mixing section and the foaming molding section. When cooling the composition, the temperature of the composition at the outlet of the cooling section is preferably 105°C to 140°C, and may be 110°C to 130°C.
[0060] In the foaming process, the foamable molten composition is extruded from the die of the foaming molding section into a low-pressure region (for example, the atmospheric pressure region), causing a rapid increase in the volume of the foaming agent and forming a styrene-based resin extruded foam.
[0061] The foam molding section may include a molding plate connected to the downstream side of the die to foam-molten foamy molten composition extruded from the die immediately after pressure release. The molding plate consists of two plate-like objects, upper and lower, and the composition extruded into the low-pressure region through a die slit, which is a linear opening in the die, foams in the space between the two molding plates, thereby obtaining a plate-shaped foam with a certain thickness. The two plate-like objects may be installed parallel to the extrusion direction, or they may be installed so that the gap gradually widens from the inlet (upstream side) to the outlet (downstream side).
[0062] The foaming pressure in extrusion foaming (the pressure applied to the foamy molten material just before it is extruded from the die slit) is, for example, around 2.5 to 15 MPa, but may also be 3 to 10 MPa or 3.5 to 8 MPa. If the foaming pressure is 2.5 MPa or higher, the foaming agent can be sufficiently dissolved in the composition, thus suppressing problems such as the foaming agent being ejected as gas from the die slit. If the foaming pressure is 15 MPa or lower, the discharge rate of the composition can be increased, thus ensuring productivity. The foaming pressure can be adjusted to the desired range by adjusting the composition supply rate (discharge rate per unit time), the die slit opening, the temperature of the die slit, etc.
[0063] [Physical properties of foams] The foam is formed, for example, into a sheet. The thickness of the sheet-shaped foam is not particularly limited and can be appropriately selected depending on the application. For example, the foam obtained by the above method can be used as insulation for houses and buildings, as well as for cold storage facilities. The foam used as insulation for these purposes preferably has a thickness of 10 mm or more in order to provide high thermal insulation and high compressive strength. The thickness of the foam may be 20 mm or more, 30 mm or more, 40 mm or more, 50 mm or more, or 60 mm or more. The thickness of the foam may also be 150 mm or less, 130 mm or less, or 120 mm or less.
[0064] In the foam of the present invention, after the shape is imparted by extrusion foam molding, the surface layer (skin layer) that was in contact with the mold may be removed by about 5 mm in the thickness direction to form the final product. However, the thickness mentioned above is the thickness of the foam before the skin layer is removed.
[0065] The foam of the present invention preferably contains 0.10 to 1.0 mol of alkyl chloride per kilogram. The presence of alkyl chloride in the foam tends to improve its heat insulation properties. On the other hand, if the alkyl chloride content is excessively high, the heat resistance of the foam may decrease due to excessive plasticization. The alkyl chloride content of the foam may be 0.15 to 0.8 mol, or 0.2 to 0.7 mol.
[0066] When considering its use as insulation for buildings and cold storage, the thermal conductivity of the foam is preferably 0.0284 W / mK or less, more preferably 0.0244 W / mK or less, and even more preferably 0.0224 W / mK or less. A lower thermal conductivity is better, but the thermal conductivity of styrene resin extruded foam is generally 0.018 W / mK or higher.
[0067] From the perspective of achieving both lightness and strength, the apparent density of the foam is 20-60 kg / m³. 3 Preferably, 25-40 kg / m 3 This is more preferable. The apparent density of the foam is calculated from the volume and mass of the foam cut into a rectangular prism.
[0068] The closed-cell ratio of the foam is preferably 90% or higher, more preferably 93% or higher, and even more preferably 95% or higher. A higher closed-cell ratio tends to result in better thermal insulation. The closed-cell diameter of the foam is determined by the true volume V1 of the foam (apparent volume minus the volume of non-closed-cell portions), the apparent volume V2 of the foam, the mass W of the foam, and the true density ρ (approximately 1.05 g / cm³ for polystyrene resins). 3 ) is calculated based on the following formula.
[0069] Closed cell ratio (%)=100×(V1-W / ρ) / (V2-W / ρ) The average cell diameter of the foam is preferably 0.05 to 0.3 mm, more preferably 0.07 to 0.24 mm, and may also be 0.1 to 0.22 mm. If the average cell diameter is excessively small, the distance between the cell walls of the foam is small, which narrows the range of motion of the cells during foam molding, making deformation difficult. This tends to make it difficult to give the extruded foam a beautiful surface and to increase the thickness of the foam. On the other hand, if the average cell diameter is large, the thermal insulation performance tends to decrease.
[0070] When the foaming ratio is high (for example, 20 times or more) and the closed-cell ratio is high as described above, the thickness of the cell walls is negligibly small compared to the cell diameter, so the average cell diameter can be estimated from the number of cells per unit length. The average cell diameter of a foam is calculated from the number of cells 'a' that intersect or touch three straight lines, each 2 mm long, drawn in the thickness direction at any point in the magnified cross-sectional image of the foam, based on the following formula.
[0071] Average bubble diameter = 2 × 3 / a The foam should preferably have excellent thermal stability and exhibit little volume change (expansion) due to heating. The volume change rate after heating the foam at 90°C for 24 hours is preferably 10% or less, and more preferably less than 5%.
[0072] The foam of the present invention has high thermal insulation properties, as well as excellent flame retardancy and heat resistance, making it suitable for use as an insulating material for houses, buildings, and cold storage facilities. [Examples]
[0073] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following embodiments.
[0074] [Making a graphite masterbatch] 48 parts by weight of polystyrene resin A (PS Japan's "PSJ-Polystyrene GPPS 680", MFR: 7.0g / 10min), 50 parts by weight of graphite (Marutoyo Casting Works' "M-885"; flake graphite, average particle size 5.5μm, fixed carbon content 89%), and 2 parts by weight of stearic acid monoglyceride (Riken Vitamin's "Rikemar S-100P") were placed in a Banbury mixer and melt-kneaded for 20 minutes under a pressure of 0.49MPa without heating or cooling. The resin temperature during kneading was 190°C. The kneaded material was supplied to a ruder, and the strand-shaped resin extruded through a die attached to the tip of the ruder at a discharge rate of 250kg / hr was cooled and solidified in a 30°C water bath, and then cut to obtain a graphite masterbatch.
[0075] [Preparation of resin mixture] Resin mixtures 1 to 8 (hereinafter referred to as "GP1" to "GP8") were prepared by dry blending polystyrene resin, the above-mentioned graphite masterbatch, flame retardant, flame retardant additive, lubricant, flame retardant, flame retardant additive, bubble diameter adjuster, stabilizer, lubricant, and absorbent according to the formulations shown in Table 1. The amount of graphite masterbatch was 4 to 5 parts by weight relative to the total of 97.6 to 98.1 parts by weight of polystyrene resin B (PS Japan's "PSJ-Polystyrene GPPS G9401", MFR: 2.1 g / 10 min) and styrene-methacrylic acid copolymer (PS Japan's "PSJ-Polystyrene G9001", methacrylic acid content: 8% by weight, MFR: 1.5 g / 10 min).
[0076] In Table 1, polystyrene resin A, graphite, and stearic acid monoglyceride are components derived from the graphite masterbatch. The amounts of each component in Table 1 are the amounts (parts by weight) blended per 100 parts by weight of the total polystyrene resin.
[0077] [Table 1] [Example 1] Extrusion foam molding was performed using a manufacturing apparatus that consisted of an extrusion molding machine in which a first extruder (single-screw extruder, 150 mm bore), a second extruder (single-screw extruder, 200 mm bore), a cooler, and a slit die (5 mm gap between the die heads) were connected in series in this order, two molding plates (upper and lower) connected downstream of the slit die of the extrusion molding machine, and a molding roll located downstream of the molding plates.
[0078] GP1 was fed from the raw material supply device at a rate of 800 kg / hr into the first extruder. Melt-kneading was performed in the first extruder at a temperature of 250°C, and the amount of foaming agent shown in Table 2 was injected under pressure near the downstream end of the first extruder. Subsequently, the composition was cooled while being kneaded in a second extruder connected to the first extruder, and further cooled to the foaming resin temperature shown in Table 2 in a cooler connected to the second extruder. The cooled composition was fed into a die slit and extruded into the atmosphere from the die slit at a foaming pressure of 4 MPa to induce foaming. It was then formed into a plate shape by passing it sequentially through a molding plate and molding rolls, obtaining a plate-shaped extruded foam with a cross-section of 60 mm thickness and 1000 mm width. Subsequently, it was cut with a cutter to a thickness of 50 mm and a width of 910 mm × length of 1820 mm.
[0079] [Examples 2-9, Comparative Examples 1-4, Reference Example 1] The type of resin mixture, the type and amount of foaming agent, the foaming temperature, and the slit die thickness were changed as shown in Tables 2 and 3. Extrusion foam molding was performed in the same manner as in Example 1 to obtain an extruded foam.
[0080] The details of the foaming agent shown in Table 2 are as follows. A sodium carbonate aqueous solution, prepared by dissolving sodium carbonate in water to a predetermined concentration, was used.
[0081] Ethyl chloride: Manufactured by Nippon Tokushu Kagaku Kogyo Co., Ltd. Water: pure water HFO-1234ze: 1,3,3,3-tetrafluoropropene, manufactured by Honeywell Japan. HCFO-1233zd: 1-chloro-3,3,3-trifluoropropene, manufactured by Honeywell Japan. Isobutane: Manufactured by Mitsui Chemicals Normal Butane: Manufactured by Iwatani Corporation
[0082] [Corrosion test using foaming agent] Mixtures with the same composition as the foaming agents used in Examples 1-9, Comparative Examples 1-4, and Reference Example 1 were sealed in a 100cc stainless steel pressure vessel along with a 2cm square, 0.1mm thick iron piece (approximately 320mg). After heating the pressure vessel at 140°C for 5 hours, the iron piece was removed, its appearance was observed and its weight measured, and its corrosiveness was evaluated according to the following criteria.
[0083] ○: The weight loss of the iron piece is less than 1 mg, and there is no change in the appearance of the iron piece. ×: Weight loss of 1 mg or more of the iron piece, or discoloration of the iron piece is observed.
[0084] [Evaluation of foam] <Amount of foaming agent remaining> The obtained foam was allowed to settle for one week in a standard atmosphere of JIS K 7100:1999 (temperature 23±5℃, relative humidity 40~70%) to allow it to recover its condition. Then, approximately 1.2 g of sample was cut from the center in both the width and thickness directions and placed in a sealable glass container with a capacity of approximately 130 cc. The container was then de-aired using a vacuum pump. After that, the container was heated to 170℃ for 10 minutes to extract the foaming agent from the foam into the container. After cooling to room temperature, helium was introduced into the container to return it to atmospheric pressure. 40 μL of gas was collected using a microsyringe, and gas chromatography analysis was performed under the following conditions. Based on a previously prepared calibration curve, the remaining amounts of foaming agents (ethyl chloride, HFO-1234ze, HCFO-1234zd, isobutane, and n-butane) in the foam were determined.
[0085] Equipment used: Shimadzu Corporation "Gas Chromatograph GC-2014" Column: "G-Column G-950 25UM" manufactured by the Chemicals Evaluation and Research Institute. Inlet temperature: 65℃ Column temperature: 80℃ Detector temperature: 100℃ Carry gas: High-purity helium Carry gas flow rate: 30 mL / min Detector: TCD Current: 120mA <Apparent Density> From the obtained foam, a test specimen measuring approximately 50 mm (or 100 mm) in thickness, 200 mm in length, and 900 mm in width was cut out. The weight of the test specimen was measured, as well as its length (in the extrusion direction), width, and thickness.
[0086] The apparent density of the foam was calculated from the measured weight and dimensions using the following formula. The unit of the apparent density was then converted to kg / m³. 3 It was converted to [a certain value].
[0087] Apparent density (g / cm³) 3 ) = Foam weight (g) / Foam volume (cm³) 3 )
[0088] <Percentage of closed cells> Test specimens measuring 40 mm thick × 25 mm long × 25 mm wide were cut from three locations: the center A in the width direction of the foam, and locations B and C 150 mm from each end in the width direction. The closed-cell ratio of each sample was determined, and the average closed-cell ratio of the three test specimens was calculated. The closed-cell ratio was determined according to procedure C of ASTM-D2856-70, using an air-comparison hydrometer (Tokyo Science Model 1000) to obtain the true volume V1 of the test specimen (apparent volume minus the volume of non-closed-cell portions), the apparent volume V2 calculated from the outer dimensions of the test specimen measured using calipers, the mass W of the test specimen, and the true density ρ of the test specimen (density of styrene resin, 1.05 g / cm³). 3 (Assuming this), the calculation was performed based on the following formula.
[0089] Closed cell ratio (%)=100×(V1-W / ρ) / (V2-W / ρ)
[0090] <Average bubble diameter> The vertical cross-sections in the width direction of the foam were observed from the extrusion direction using the aforementioned microscope (Keyence "DIGITAL MICROSCOPE VHX-900") at three locations: the center in the width direction and 150 mm from one end to the opposite end in the width direction (the same location at both ends in the width direction). 100x magnified photographs were taken. Similarly, the vertical cross-sections in the extrusion direction of the three locations in the width direction of the thickness direction were observed from the width direction using the same microscope, and 100x magnified photographs were taken. Three 2 mm straight lines were drawn arbitrarily in the thickness direction of the magnified photographs (three lines for each observation location and each observation direction), and the number of bubbles intersecting these lines or forming straight-line bubbles was measured. From the measured number of bubbles a, the average bubble diameter A in the thickness direction for each observation location was calculated using the following formula (1). The average value of the three locations (two directions for each location) was taken as the average bubble diameter A (average value) in the thickness direction of the styrene resin extruded foam.
[0091] The average bubble diameter A (mm) in the thickness direction for each observation point = 2 × 3 / number of bubbles a
[0092] <Bubble deformation rate> The cross-section perpendicular to the extrusion direction at three locations in the thickness direction of the foam—the center in the width direction and 150 mm from one end to the opposite end in the width direction (the same location at both ends in the width direction)—was observed from the width direction using the aforementioned microscope, and 100x magnified photographs were taken. Three 2 mm straight lines were drawn arbitrarily in the extrusion direction of the magnified photographs (three lines for each observation location), and the number of bubbles b tangent to these lines was measured. From the measured number of bubbles b, the average bubble diameter B in the extrusion direction for each observation location was calculated using the following equation (2). The average value of the three locations was taken as the average bubble diameter B (average value) in the extrusion direction of the styrene resin extruded foam.
[0093] The average bubble diameter B (mm) in the extrusion direction for each observation point = 2 × 3 / number of bubbles b ... (2) A cross section perpendicular to the width direction at the center in the thickness direction was observed from the extrusion direction using the aforementioned microscope at a total of 3 locations: the center in the width direction of the obtained styrenic resin extruded foam, and a position 150 mm from one end in the width direction toward the opposite end (the same position for both ends in the width direction), and a 100× magnified photograph was taken. Three arbitrary 2 mm straight lines were drawn in the width direction of the magnified photograph (3 lines for each observation location), and the number c of cells in contact with the straight lines was measured. From the measured number c of cells, the average cell diameter C in the width direction for each observation location was determined by the following formula (3). The average value of the 3 locations was defined as the average cell diameter C (average value) in the width direction of the styrenic resin extruded foam.
[0094] Average cell diameter C (mm) in the width direction per observation location = 2 × 3 / number of cells c ··· (3)
[0095] The cell deformation ratio was determined by the following formula (4) from the aforementioned average cell diameter.
[0096] Cell deformation ratio (dimensionless) = A (average value) / {[B (average value) + C (average value)] / 2} ··· (4)
[0097] <Thermal Conductivity> In accordance with JIS A 9521, a test piece cut out from the foam with dimensions of 50 mm (or 100 mm) in thickness × 300 mm in length (extrusion direction) × 300 mm in width was used, and the thermal conductivity at an average temperature of 23°C was measured using a thermal conductivity measuring device (Eiko Seiki Co., Ltd., HC-074). Specifically, after the production of the foam, a test piece of the above dimensions was cut out, and the test piece was subjected to the standard temperature condition class 3 (23°C ± 5°C) and standard humidity condition class 3 (50 +20、-10 % R.H.) specified in JIS K 7100, and then the thermal conductivity was measured one week (after 7 days had elapsed) after the production of the foam.
[0098] <JIS Flammability> In accordance with JIS A 9521:2017, a test specimen measuring 10 mm thick x 200 mm long (extrusion direction) x 25 mm wide was cut from the center of the widthwise direction of the foam immediately after manufacturing, and conditioned by standing in a standard atmosphere of JIS K 7100:1999 Class 3 for one week. When the flammability of the conditioned samples was evaluated, the samples of Examples 1-9, Comparative Examples 1-4, and Reference Example 1 all met the criteria of "flame extinguishing within 3 seconds, no residue, and not burning beyond the flammability limit indicator."
[0099] <Exterior> The appearance of the foam with the skin layer intact (before cutting) and the foam with the skin layer removed by 5 mm in the thickness direction from both the upper and lower surfaces (after cutting) were visually evaluated. In all of the samples from Examples 1-9, Comparative Examples 1-4, and Reference Example 1, the foam before cutting was flat and without any warping, and no surface abnormalities such as flow marks or tearing were observed before or after cutting, indicating a good appearance.
[0100] <Stomatal formation rate> The surfaces of 100 obtained foams were observed and evaluated according to the following criteria.
[0101] ○: 0 or 1 sheet has pores with a diameter of 2 mm or more on the surface. △: Two or three pieces with pores of 2 mm or larger in diameter on the surface. ×: Four or more items with pores of 2mm or larger in diameter on the surface. Tables 2 and 3 show the type of resin mixture used in each example, comparative example, and reference example, the amount of foaming agent injected (weight relative to 100 parts by weight of polystyrene resin, and molar amount per 1 kg of foam), the evaluation results of corrosiveness due to the foaming agent, the foaming temperature, and the evaluation results of the foam.
[0102] [Table 2]
[0103] [Table 3] As can be seen from Examples 1-9 and Comparative Examples 1-4, by using a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and their derivatives, it is possible to easily obtain styrene-based resin extruded foam with excellent heat insulation properties, a beautiful surface, and no pores. Reference Example 1 did not contain an acid neutralizing agent, so metal corrosion due to the foaming agent was observed.
Claims
1. A method for producing a styrene resin extruded foam, comprising melt-kneading a composition containing a styrene resin and a foaming agent, and extruding it to a low-pressure range to perform foam molding, The foaming agent comprises at least alkyl chloride and water. The aforementioned composition further comprises an acid neutralizing agent. The preceding composition further comprises a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and / or derivatives thereof. A method for producing polystyrene resin extruded foam.
2. The method for producing a polystyrene resin extruded foam according to claim 1, wherein the amount of a nitrogen-containing compound selected from the group consisting of cyanuric acid, isocyanuric acid, and derivatives thereof in the composition is 0.1 parts by weight or more per 100 parts by weight of the styrene resin.
3. A method for producing a polystyrene resin extruded foam according to any one of claims 1 to 2, wherein the amount of alkyl chloride in the composition is 1 to 8 parts by weight per 100 parts by weight of the styrene resin.
4. The blowing agent further contains hydrofluoroolefin and / or hydrochlorofluoroolefin, A method for producing a styrene resin extruded foam according to any one of claims 1 to 2, wherein the total amount of hydrofluoroolefin and / or hydrochlorofluoroolefin added is 0.5 parts by weight or more and 10.0 parts by weight or less per 100 parts by weight of styrene resin.
5. The composition contains graphite, A method for producing a styrene resin extruded foam according to any one of claims 1 to 2, wherein the graphite is contained in an amount of 1.0 part by weight or more and 5.0 parts by weight or less per 100 parts by weight of the styrene resin.
6. A method for producing a polystyrene resin extruded foam according to any one of claims 1 to 2, wherein the thermal conductivity of the foam is 0.0284 W / mK or less.
7. A method for producing a polystyrene resin extruded foam according to any one of claims 1 to 2, wherein the thickness of the foam is 10 mm or more.
Citation Information
Patent Citations
Styrenic resin extrusion foaming product and its production method
JP2005330351A
Styrenic resin extrusion foamed body and manufacturing method thereof
JP2019108416A
Styrenic resin extrusion expanded material
JP2019189811A
Production method of polystyrene resin extrusion expanded material
JP2024141462A